2019
DOI: 10.3390/su11143863
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors Influencing Consumers’ Purchase of Electric Vehicles

Abstract: Although the rapid progress of the global economy and technology has advanced human civilization, it has also caused tremendous damage to the global ecological environment. Therefore, humans are thinking seriously about the environment and its sustainable development. One of the solutions to environmental problems is new energy vehicles. Since the promulgation of the "Energy Saving and New Energy Vehicle Industry Development Plan (2012-2020)" by the General Office of the State Council, the Chinese government h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
110
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 33 publications
12
110
2
8
Order By: Relevance
“…An interesting manuscript "The effect of perceived risk on the purchase intention of electric vehicles: an extension to the technology acceptance model" (Thilina, 2019) seeks to analyze significant market penetration for the sale of electric vehicles accompanied by the analysis (Mo, 2018) of life-cycle cost of ownership including congestion and environmental impacts (Tu, 2019), (Rajeev, et al, 2019), (Hao, 2017), (Philipsen, et al, 2019), (Lopez-Arboleda, et al, 2019), (Almeida, et al, 2019). Considerable emphasis have been placed on improvements in vehicle charging (Wolbertus, et al, 2019) amongst many other underlying technological areas seeking to improve the value proposition to potential buyers (Jager, et al, 2019), , , (Minnerup, et al, 2019), (Muller, 2019) and also make recommendations in both technology (Zha, et al, 2019), , (Zha, et al, 2019), , (Jiyan, et al, 2019), (Pier, et al, 2019), (Agaton, et al, 2019), , (Watanabe, et al, 2019), (Kusaka, et al, 2019), (Zhang, W., et al, 2019), , (Mayer, et al, 2019), (Ricciardi, et al, 2019), , (Yu, Z., et al, 2019), (Senda, et al, 2019), (Marquez-Fernandez, et al, 2019), (Wu, D., et al, 2019), (Wang, H., et al, 2019), (Obayashi, et al, 2019), (Gong, et al, 2019), (Vermeulen, et al, 2019), (Jia, J., et al, 2019), (Li, Q., et al, 2019) and policy incentives (Zhang, X., et al, 2019), (Ortar, et al, 2019), culminating in charging strategies to influence the obvious trade-off between gasoline prices and charging availability , (Wolbertus, et al, 2019),…”
Section: Materials (Literature Review)mentioning
confidence: 99%
“…An interesting manuscript "The effect of perceived risk on the purchase intention of electric vehicles: an extension to the technology acceptance model" (Thilina, 2019) seeks to analyze significant market penetration for the sale of electric vehicles accompanied by the analysis (Mo, 2018) of life-cycle cost of ownership including congestion and environmental impacts (Tu, 2019), (Rajeev, et al, 2019), (Hao, 2017), (Philipsen, et al, 2019), (Lopez-Arboleda, et al, 2019), (Almeida, et al, 2019). Considerable emphasis have been placed on improvements in vehicle charging (Wolbertus, et al, 2019) amongst many other underlying technological areas seeking to improve the value proposition to potential buyers (Jager, et al, 2019), , , (Minnerup, et al, 2019), (Muller, 2019) and also make recommendations in both technology (Zha, et al, 2019), , (Zha, et al, 2019), , (Jiyan, et al, 2019), (Pier, et al, 2019), (Agaton, et al, 2019), , (Watanabe, et al, 2019), (Kusaka, et al, 2019), (Zhang, W., et al, 2019), , (Mayer, et al, 2019), (Ricciardi, et al, 2019), , (Yu, Z., et al, 2019), (Senda, et al, 2019), (Marquez-Fernandez, et al, 2019), (Wu, D., et al, 2019), (Wang, H., et al, 2019), (Obayashi, et al, 2019), (Gong, et al, 2019), (Vermeulen, et al, 2019), (Jia, J., et al, 2019), (Li, Q., et al, 2019) and policy incentives (Zhang, X., et al, 2019), (Ortar, et al, 2019), culminating in charging strategies to influence the obvious trade-off between gasoline prices and charging availability , (Wolbertus, et al, 2019),…”
Section: Materials (Literature Review)mentioning
confidence: 99%
“…The factors influencing vehicle choice in general and EVs in particular can be studied using empirical and theoretical models. An example of the latter is provided by Tu and Yang [7], who attempted to combine three pieces of theory: theory of planned behavior, technology acceptance model and innovation diffusion theory. Table 1 shows the list of such factors identified in three studies: Mueller and de Haan [8], Jensen et al [9] and Struben and Sterman [10].…”
Section: Literaturementioning
confidence: 99%
“…However, the review also showed that this analysis is very suitable for equally complex systems in other domains such as the space industry, business management, policy analysis, and energy and environment domains. Most of the literature in this study (41) included peer-reviewed papers, conference proceedings, and book chapters. The authors also included relevant PhD and master theses (3), project reports (9), and web pages (11) to reduce the elimination bias of search engines.…”
Section: Kth Library and Googlementioning
confidence: 99%
“…It is helpful and necessary for stakeholders to engage a broad range of individuals including local politicians, media, residents, business owners, and national pressure groups due to the sensitivity of transportation strategy development [40]. Stakeholder requirements play a crucial role when the system reaches the implementation stage in society [41].In the case of this ERS study, knowing the stakeholders' concerns, what goals they set for themselves, and how they act to reach their goals can help uncover interactions, similarities, and conflicts among the stakeholders. Actor analysis methods focus on analysing the actors' interactions in the policy analysis domain, which provides a chance to understand system complexity from the actor perspective [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation